Hydrochloric acid plant design - Roque, Arturo C. (College of Engineering, 1963)
This design is about the production of Hydrochloric acid from common salt. The process is really quite simple. The first step is the purification of salt. Then, the purified salt is broken up into sodium metal, a by-product of the process, and chlorine gas. The chlorine gas obtained is then reached with hydrogen gas forming the acid as a gas. The acid gas is further purified, packed in cylinders and finally shipped. The plant has maximum capacity of 1,815,000 pounds of anhydrous hydrochloric acid annually or 6050 pounds daily. Operation is continuous, 24 hours a day, 6 days a week. Salt consumption amounts to 9650 pounds daily. Aside from salt, other raw materials are sodium carbonate, calcium hydroxide and barium chloride. Equipments will have to be imported mainly from U.S.A. Some are available locally. Some are fabricated on site. Heat exchangers are used. We will have a boiler of our own for steam generation as well as two water reservoirs. All equipments and other accessories like pumps and pipes have been specified. Capital investment amounts to P7,091,924 broken up as follows : Fixed capital - P1,178,576, Working capital P594,403 Annual sales amount to P4,149,304. Break even point at 30.1 percent. Shut down point at 8.8 percent of level of production. Percent return on investment is 20 percent. To maintain this percentage, the level of production should be at least 86 percent. Payout time is 3.33 years. Annual maximum profit is P1,772,684. Selling price of HCl is P2.00 per pound of anhydrous acid. Market survey shows favorable trend for HCl. It has a good future in this country. There is practically no competition as far as we can see because no major plant is producing HCl in large scale although there is one or two which are producing HCl as a by-product. Finally, we conclude that it is quite possible and profitable to establish this plant here.